Concrete workability and water resistance improvement using polymeric admixtures - Pires, Patrício (2006)
The present work aims to compare the physical and mechanical properties of concrete produced with different incorporation of polymeric admixtures. Two families of admixtures are studied: the superplasticizers and water resisting admixtures. The main results of the experimental program are presented and analysed. The performance of concrete incorporating admixtures is measured using physical and mechanical properties. Properties such as compressive strength, air content, water/cement ratio (W/C), density and, in the case of water resisting admixtures, the capillary absorption were measured.